WHAT STUDENTS FROM FACULTIES OF PHYSICAL EDUCATION AND SPORT THINK ABOUT PRACTICAL LESSONS IN SKIING - Rašid Hadžić; Georgi Georgiev; Dobrislav Vujović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The survey was conducted on a sample of 116 students from the Faculties of Physical Education and Sport in Niksic and Novi Pazar (88 students from Niksic and 28 students from Novi Pazar). The questionnaire has 13 questions about students' attitude towards practical lessons in skiing. The answers are processed with the non-parametric test of Mann-Whitney. Statistically significant difference in the attitudes is established only with the attitude number 13: 'I engaged myself in the skiing to the best of my ability', and the difference is in favor of the students Faculties of Physical Education and Sport from Niksic.